Carbon fiber composite voice diaphragm and preparation method and application thereof
By using the composite technology of carbon fiber and aramid nanofiber in the speaker sound film material, the problems of large thickness, low strength and modulus of existing carbon fiber materials are solved, and the efficient energy conversion of tweeters and the expansion of frequency response range are achieved.
Patent Information
- Application Number
- CN202510049342.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
In speaker applications, existing carbon fiber materials have problems such as large thickness, low strength and modulus and high glue content, which are difficult to meet the performance needs of tweeter sound film materials.
The design of carbon fiber, aramid nanofiber, epoxy resin, curing agent and its specific proportions are used to obtain a composite felt of carbon fiber-aramid nanofibers through wet molding process, and then infiltrate the epoxy resin and curing agent and then press and shape it hot-press to prepare a carbon fiber composite sound film with a small thickness and a high Young's modulus.
The thickness reduction, strength and modulus of the carbon fiber composite sound film are achieved, and it has suitable damping performance. When applied to treble top speakers, the transient response, energy conversion efficiency and sensitivity of the speaker are improved, segmentation vibration and phase distortion are reduced, and the frequency response range is expanded.
Smart Images

Figure BDA0005239507980000031 
Figure BDA0005239507980000121 
Figure BDA0005239507980000122
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of loudspeakers, and in particular relates to a carbon fiber composite sound membrane and a preparation method and application thereof. Background Art
[0002] A tweeter is an audio device specially designed to play high-frequency sounds. The material properties of the diaphragm have a crucial impact on the sensitivity, frequency response range, and smoothness of the frequency response curve of the tweeter. Generally, the diaphragm material needs to meet the following requirements: a. The thickness of the diaphragm should be thin or the density should be small, which can reduce the total vibration mass of the speaker and improve the sensitivity of the speaker; b. The Young's modulus of the diaphragm material should be large; increasing the Young's modulus can reduce the split vibration and phase distortion of the unit and increase the frequency response range of the unit; c. The diaphragm has appropriate internal damping; appropriate internal damping can also suppress the split vibration and make the frequency response characteristics relatively flat.
[0003] Common tweeter diaphragm materials include the following categories: (1) Silk diaphragm: It is a more traditional tweeter diaphragm material, usually used to enhance the high-frequency response and resolution. The price of silk diaphragm is relatively low and its service life is long, but its elasticity is poor, resulting in some obvious defects in sound quality, such as local resonance. (2) PEI diaphragm: It is a newer tweeter diaphragm material with good high-temperature stability, so it can be used in high-power occasions. Compared with silk diaphragm, PEI diaphragm has better elasticity and higher resonance frequency. At the same time, it will also produce fewer color bands in the tone and the sound accuracy is relatively higher. (3) Metal diaphragm: It has good rigidity and when used in tweeters, the sound is brighter and clearer. However, the existing PEI diaphragms and metal diaphragms have performance defects to varying degrees in terms of mechanical properties and acoustic properties, which affect the sound effect of tweeters.
[0004] In recent years, carbon fiber has been widely used in the field of speakers due to its good rigidity. Carbon fiber has excellent performance, high axial strength and modulus, 20 times the strength of steel, 2-3 times the tensile modulus of steel, only 1 / 4 of the specific gravity of steel, 7.9 times the tensile strength of steel, and about 3 times the Young's modulus of traditional glass fiber and about 2 times that of Kevlar fiber (KF-49). At the same time, carbon fiber does not dissolve or swell in organic solvents, acids, and alkalis, and has outstanding corrosion resistance. Therefore, carbon fiber materials, with their advantages of light weight, high strength and rigidity, and strong designability, not only meet people's requirements for product quality, but also meet the application needs of lightweight. It is an ideal material for speakers. The use of vibration systems containing carbon fiber has gradually become a trend in the speaker industry.
[0005] At present, the carbon fiber materials used in the speaker field can be divided into the following categories: First, single-layer carbon fiber woven cloth is surface-treated and used for the sound cone in car audio. This type of carbon fiber cone has good weather resistance, but its strength and air tightness still need to be improved; second, the sound cone is composed of carbon fiber cloth / carbon fiber board and foam core layer into a sandwich structure. This type of carbon fiber composite cone has a higher specific modulus and also exhibits good acoustic performance, but its overall thickness is relatively thick, which limits its application in thin and light products; third, the sound cone is hot-pressed from carbon fiber prepreg. This type of carbon fiber cone has a higher resin content and a higher thickness, and is limited by the elongation of the carbon fiber prepreg, so it is impossible to form a carbon fiber cone with a complex curved surface.
[0006] CN115895191A discloses an ultra-thin carbon fiber sound basin, the raw materials for its preparation include the following components by weight: 90-100 parts of carbon fiber woven cloth, 7-28 parts of epoxy resin, 3-12 parts of curing agent, 0.0001-5 parts of color paste, and 0.1-1 parts of defoaming agent; the carbon fiber sound basin has high strength and good moisture resistance, and can be processed in various shapes and colors to show different characteristics in appearance. However, due to the limitation of the thickness of the carbon fiber woven cloth raw material itself, the carbon fiber sound basin prepared by this method still has the problem of large thickness.
[0007] CN114979930A discloses a method for producing a loudspeaker diaphragm dome, comprising the following steps: S1: spraying a mold release agent on the mold; S2: cutting a carbon fiber layer and placing it in the lower membrane cavity of the mold, wherein the carbon fiber layer is composed of a carbon fiber surface felt and a matrix, or a three-layer carbon fiber unidirectional tape prepreg is used; S3: closing the mold, heating and curing the carbon fiber layer; S4: demolding and molding after curing. The composite material prepared by this method has high strength, firm bonding of adhesive materials, good heat resistance, and excellent sound quality in the high-frequency range above the kHz high frequency band.
[0008] Although carbon fiber has the advantages of high strength and high modulus, its surface is smooth and has no active functional groups, so the interweaving and bonding forces between fibers are very poor, resulting in low strength and modulus, large thickness, and high glue content in speaker composite materials using carbon fiber woven cloth and carbon fiber prepreg, which are difficult to meet the performance requirements of tweeter sound membrane materials. Based on this, developing a carbon fiber sound membrane material with low thickness and high Young's modulus to meet the application requirements of tweeters is an urgent problem to be solved in this field. Summary of the invention
[0009] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a carbon fiber composite sound membrane and a preparation method and application thereof. Through the design of carbon fiber, aramid nanofiber, epoxy resin, and curing agent and their compounding in a specific proportion, the carbon fiber composite sound membrane has a small thickness, a high Young's modulus, and suitable damping. When it is applied to a tweeter dome speaker, the speaker has good transient responsiveness, high energy conversion efficiency, and high sensitivity, which can reduce the split vibration and phase distortion of the unit and improve the frequency response range of the unit.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a carbon fiber composite sound membrane, wherein the raw materials for preparing the carbon fiber composite sound membrane include the following components in parts by mass:
[0012]
[0013] Aramid fiber is a synthetic fiber composed of aromatic polyamide molecules, which has excellent properties such as high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight, but traditional aramid fiber also has problems such as smooth surface, strong inertia, weak composite interface strength, and difficult processing. The present invention adopts aramid nanofiber, which has a large specific surface area, high surface energy, and good dispersibility. It can be used as a filling and reinforcing material and is evenly dispersed in a network structure with carbon fiber as the main body, playing the role of wrapping, winding, and increasing binding sites, and forming an excellent interweaving and winding effect with carbon fiber, thereby playing a filling and reinforcing role.
[0014] The present invention adopts carbon fiber as the main substrate and aramid nanofiber as the filling and reinforcing material, obtains a composite felt of carbon fiber-aramid nanofiber through a wet molding process, and then impregnates epoxy resin and curing agent and hot presses to obtain the carbon fiber composite sound membrane. Through the design of carbon fiber, aramid fiber, epoxy resin, and curing agent and their compounding in a specific proportion, and combined with a specific preparation process, the thickness of the carbon fiber composite sound membrane is thinner, breaking through the thickness limit of the carbon fiber woven cloth and carbon fiber prepreg raw materials themselves; at the same time, the carbon fiber composite sound membrane has high strength, high Young's modulus, suitable loss factor and moderate damping. When it is applied to a tweeter dome speaker, the speaker has good transient response, high energy conversion efficiency, high sensitivity, can reduce the split vibration and phase distortion of the unit, and improve the frequency response range of the unit.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] In the preparation raw materials of the present invention, the mass parts of the carbon fiber are 85-95 parts, for example, it can be 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts or 94 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0017] The mass proportion of the aramid nanofiber is 5-15 parts, for example, it can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0018] The mass parts of the epoxy resin are 5-15 parts, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0019] The mass parts of the curing agent are 1.5-4.5 parts, for example, it can be 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts or 4.4 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0020] Preferably, the average length of the carbon fiber is 2-4 mm, for example, it can be 2.2 mm, 2.4 mm, 2.5 mm, 2.8 mm, 3 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm or 3.8 mm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0021] As a preferred technical solution of the present invention, the carbon fiber is chopped carbon fiber, and further preferably the average length is 2-4 mm. As the main substrate of the sound membrane, it is conducive to the uniform dispersion of the carbon fiber.
[0022] Preferably, based on the total mass of the carbon fiber and the aramid nanofiber as 100%, the mass of the carbon fiber is 85-95%, for example, it can be 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93% or 94%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0023] In the present invention, the aramid nanofibers are obtained by mechanized treatment of aramid fibers; the mechanical action fibrillates the aramid fibers to form the aramid nanofibers with larger specific surface area and higher surface energy.
[0024] Since aramid fibers usually have a skin-core structure of dry-jet wet spinning, the strong atomic bonds along the axial direction and the weak intermolecular bonds along the radial direction of the aramid fiber molecular chain make it have obvious strength anisotropy, so the epidermis of the aramid fiber can be easily peeled off along the fiber axis under the action of mechanical vibration force. The aramid nanofibers described in the present invention are made of aramid fibers as raw materials, which are finely fibrillated by mechanized treatment (mechanical action), and a large number of fine fibers are peeled off along the axial direction.
[0025] Preferably, the aramid fiber includes meta-aramid fiber and / or para-aramid fiber, and para-aramid fiber is more preferred.
[0026] Preferably, the diameter of the aramid nanofiber is 500-990nm, for example, it can be 520nm, 550nm, 580nm, 600nm, 620nm, 650nm, 680nm, 700nm, 720nm, 750nm, 780nm, 800nm, 820nm, 850nm, 880nm, 900nm, 920nm, 950nm or 980nm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0027] Preferably, the aspect ratio of the aramid nanofiber is 2200-3000, for example, it can be 2300, 2400, 2500, 2600, 2700, 2800 or 2900, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0028] Preferably, the epoxy resin comprises epoxy laminating resin.
[0029] In the present invention, the curing agent is an epoxy resin curing agent, which can react with epoxy groups.
[0030] Preferably, the curing agent includes an amine curing agent and / or a phenolic curing agent.
[0031] Preferably, the amine curing agent includes any one of 1,3-cyclohexanedimethylamine, ethylene glycol bis(3-aminopropyl) ether, and polyetheramine (α-(2-aminomethylethyl)-ω-(2-aminomethylethoxy)polyethylene glycol) or a combination of at least two thereof.
[0032] Preferably, the phenolic curing agent includes any one of bisphenol A, bisphenol F, and bisphenol S, or a combination of at least two of them.
[0033] Preferably, the mass ratio of the epoxy resin to the curing agent is 1:(0.2-0.4), for example, it can be 1:0.22, 1:0.24, 1:0.25, 1:0.26, 1:0.28, 1:0.3, 1:0.32, 1:0.34, 1:0.35, 1:0.36 or 1:0.38, etc., and more preferably 1:(0.28-0.32).
[0034] Preferably, the thickness of the carbon fiber composite sound membrane is ≤0.12mm, for example, it can be 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm or 0.11mm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 0.06-0.1mm is further preferred.
[0035] Preferably, the Young's modulus of the carbon fiber composite sound membrane is ≥21GPa, for example, it can be 21.5GPa, 22GPa, 22.5GPa, 23GPa, 23.5GPa, 24GPa, 24.5GPa, 25GPa, 25.5GPa, 26GPa, 26.5GPa, 27GPa, 27.5GPa, 28GPa, 28.5GPa, 29GPa or 30GPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 22-29GPa is further preferred.
[0036] Preferably, the loss factor of the carbon fiber composite sound membrane is 0.01-0.03, for example, it can be 0.012, 0.015, 0.016, 0.018, 0.02, 0.022, 0.024, 0.025, 0.026 or 0.028, as well as specific point values between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 0.015-0.028 is further preferred.
[0037] In a second aspect, the present invention provides a method for preparing the carbon fiber composite sound membrane as described in the first aspect, the preparation method comprising:
[0038] Dispersing aramid fibers in water for pulping to obtain aramid nanofiber slurry;
[0039] Evenly mixing the aramid nanofiber slurry and the carbon fiber to obtain a mixed solution;
[0040] The mixed solution is filtered and dried to obtain a sound membrane blank;
[0041] The sound membrane blank is immersed in epoxy glue and then hot-pressed to obtain the carbon fiber composite sound membrane; the epoxy glue includes a combination of epoxy resin and curing agent.
[0042] In the preparation method of the present invention, aramid fiber is firstly subjected to pulping treatment to obtain aramid nanofiber slurry; aramid fiber usually has a skin-core structure of dry-jet wet spinning, and the strong atomic bonds along the axial direction and the weak intermolecular bonds along the radial direction of the aramid fiber molecular chain make it have obvious strength anisotropy, so the epidermis of the aramid fiber can be easily peeled off along the fiber axis under the action of mechanical vibration force, and a large number of fine fibers with high degree of fibrillation (preferably with a diameter of 500-990nm) are peeled off along the axial direction to obtain aramid nanofibers with large specific surface area, high surface energy and good dispersibility. The aramid nanofibers are compounded with carbon fiber substrate as filling and reinforcing materials, uniformly dispersed in the substrate structure, and formed into a sound film blank through a wet molding process, and then impregnated with epoxy glue and hot-pressed for finalization, and the epoxy resin undergoes a curing reaction with the curing agent during the hot pressing process, and plays a bonding role between the carbon fiber and the aramid nanofiber, so that the structure of the obtained carbon fiber composite sound film is complete and dense, and has high strength and high modulus.
[0043] Preferably, the aramid fiber includes meta-aramid fiber and / or para-aramid fiber, and para-aramid fiber is more preferred.
[0044] Preferably, the beating is performed by a Valley beater.
[0045] Preferably, the beating time is 5-16 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0046] Preferably, during the beating process, the gap between the flying knife and the bottom knife is 0.1-0.2 mm, for example, it can be 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm or 0.19 mm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0047] As a preferred technical solution of the present invention, aramid fibers are dispersed in water and are beaten by a Wally beater, with the gap between the flying knife and the bottom knife of the beater being 0.1-0.2 mm, so that the flying knife and the bottom knife have no shearing effect on the aramid fibers during the beating process. The aramid fibers are rubbed against each other to cause the highly oriented cortex of the aramid fibers to fall off, and the microfibrils of the core layer to be drawn out, forming fluffy filaments that are coiled around the trunk, thereby generating a large number of fluffy microfibers on the surface of the aramid fibers, thereby maximizing the degree of fibrilization of the aramid fibers, and obtaining aramid nanofibers with a diameter of 500-990 nm and an aspect ratio of 2200-3000.
[0048] For example, the diameter and aspect ratio of the aramid nanofibers can be obtained by scanning electron microscopy (SEM) testing.
[0049] Preferably, the aramid nanofiber slurry and carbon fiber are dispersed in water and mixed evenly to obtain a mixed solution.
[0050] Preferably, the mixing is performed by a stirrer so that the carbon fibers are wrapped and entangled by the aramid nanofibers.
[0051] Preferably, the stirring speed of the mixing is 1000-5000rpm, for example, it can be 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or 4500rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0052] Preferably, the mixed solution is diluted with water and then filtered to obtain a wet blank; the wet blank is dried to obtain a sound membrane blank.
[0053] Preferably, the filtering method includes suction filtration, thereby making the composite wet blank of the carbon fiber and the aramid nanofiber more compact. After the wet blank is dried, a sound membrane blank with a certain pore structure is obtained.
[0054] Preferably, the filtration pressure is 0.1-0.3 MPa, for example, it can be 0.12 MPa, 0.15 MPa, 0.18 MPa, 0.2 MPa, 0.22 MPa, 0.25 MPa or 0.28 MPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Preferably, the drying temperature is 80-120°C, for example, it can be 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or 115°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Preferably, the impregnation is carried out under vacuum conditions, so that the epoxy adhesive completely penetrates into the pores of the sound membrane blank, so that the carbon fiber, aramid nanofiber and epoxy adhesive are tightly combined.
[0057] Preferably, the immersion time is 1-15 min, for example, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min or 14 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 2-8 min is further preferred.
[0058] Preferably, the temperature of the hot pressing and setting is 150-200°C, for example, it can be 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C or 195°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Preferably, the hot pressing time is 20-60 min, for example, it can be 25 min, 28 min, 30 min, 32 min, 35 min, 38 min, 40 min, 42 min, 44 min, 45 min, 50 min or 55 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 30-45 min is further preferred.
[0060] As a preferred technical solution of the present invention, the method for preparing the carbon fiber composite sound membrane comprises the following steps:
[0061] The aramid fibers are dispersed in water for beating, wherein the gap between the flying knife and the bottom knife is controlled to be 0.1-0.2 mm during the beating process, and the beating time is 5-16 hours to obtain an aramid nanofiber slurry;
[0062] Dispersing the aramid nanofiber slurry and carbon fiber in water, and mixing them evenly under stirring conditions of 1000-5000 rpm to obtain a mixed solution;
[0063] The mixed solution is diluted with water and then filtered by suction to obtain a wet blank;
[0064] Drying the wet blank at 80-120° C. to obtain a sound membrane blank;
[0065] The sound membrane blank is placed in epoxy glue, immersed under vacuum conditions, and then hot-pressed at 150-200° C. for 20-60 minutes to obtain the carbon fiber composite sound membrane.
[0066] In a third aspect, the present invention provides a loudspeaker, comprising the carbon fiber composite sound membrane as described in the first aspect.
[0067] Preferably, the speaker is a tweeter.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] In the carbon fiber composite sound membrane provided by the present invention, carbon fiber is used as the main substrate, aramid nanofiber is used as the filling and reinforcing material, and a composite felt of carbon fiber-aramid nanofiber is obtained by a wet molding process, and then hot-pressed after being impregnated with epoxy resin and a curing agent to obtain a carbon fiber composite sound membrane with a high carbon fiber content. The thickness is thinner, as low as 0.07-0.1mm, breaking through the thickness limit of the carbon fiber woven cloth and carbon fiber prepreg raw materials themselves. The carbon fiber composite sound membrane has high strength, high Young's modulus, suitable loss factor and moderate damping. When it is applied to a tweeter dome speaker, the speaker has good transient responsiveness, high energy conversion efficiency, high sensitivity, can reduce the split vibration and phase distortion of the unit, and improve the frequency response range of the unit. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0071] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0072] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.
[0073] In the following examples of the present invention, the specific information of the materials used is as follows:
[0074]
[0075] The carbon fiber composite sound membrane and the preparation method thereof described in the present invention will be described in detail below using multiple embodiments as examples, but the carbon fiber composite sound membrane and the preparation method thereof described in the present invention are not limited to these embodiments.
[0076] Example 1
[0077] A carbon fiber composite sound membrane, the raw materials for its preparation include the following components in parts by mass:
[0078]
[0079] The average length of the carbon fiber is 3 mm. The preparation method of the carbon fiber composite sound membrane comprises the following steps:
[0080] (1) dispersing para-aramid fibers in water and beating them with a Wally beater, during which the gap between the flying knife and the bottom knife is controlled to be 0.1 mm, and the beating time is 12 h, to obtain aramid nanofiber slurry;
[0081] (2) dispersing the aramid nanofiber slurry and the carbon fiber in water, and stirring and mixing them evenly with a stirrer at a rotation speed of 3000 rpm to obtain a mixed solution;
[0082] (3) diluting the mixed solution with water and filtering it by suction filtration at a pressure of 0.2 MPa to obtain a wet blank;
[0083] (4) placing the wet blank in a blast drying oven and drying at 105° C. to obtain a sound film blank;
[0084] (5) Evenly mix the epoxy resin and the curing agent to obtain epoxy adhesive solution; place the sound membrane blank in the epoxy adhesive solution, immerse it in a vacuum condition for 5 minutes, and then hot-press and shape it at 180° C. for 30 minutes to obtain the carbon fiber composite sound membrane.
[0085] Examples 2-7, Comparative Examples 1-5
[0086] A carbon fiber composite sound membrane, which differs from Example 1 only in that the raw materials used in its preparation are different, as specifically shown in Table 1; in Table 1, the unit of dosage of the raw materials used in its preparation is "part"; items not shown in Table 1 are the same as those in Example 1.
[0087] Table 1
[0088]
[0089]
[0090] Comparative Example 6
[0091] A carbon fiber composite sound membrane, which differs from Example 1 only in that the aramid nanofiber is replaced by an equal mass of para-aramid fiber, that is, the pulping treatment of step (1) is not performed in the preparation method, and the para-aramid fiber is directly mixed with the carbon fiber to obtain a mixed liquid, and the other steps and process parameters are the same as those in Example 1.
[0092] Comparative Example 7
[0093] A carbon fiber composite sound membrane, which differs from Example 1 only in that the aramid nanofiber is replaced by an equal mass of aramid powder, that is, the pulping treatment of step (1) is not performed in the preparation method, and the aramid powder is directly mixed with the carbon fiber to obtain a mixed liquid, and the other steps and process parameters are the same as those in Example 1.
[0094] Comparative Example 8
[0095] A carbon fiber composite sound membrane, which differs from Example 1 only in that the composition of epoxy resin and curing agent is replaced by phenolic resin, that is, 13 parts of phenolic resin are used in the preparation raw material, and step (5) of the preparation method is to immerse it in phenolic resin glue, and the other steps and process parameters are the same as Example 1.
[0096] Comparative Example 9
[0097] A carbon fiber composite sound membrane, which differs from Example 1 only in that the composition of epoxy resin and curing agent is replaced by water-based polyurethane resin, that is, 13 parts of water-based polyurethane resin are used in the preparation raw materials, and step (5) of the preparation method is to immerse in water-based polyurethane glue, and the other steps and process parameters are the same as those in Example 1.
[0098] The following performance tests were performed on the carbon fiber composite sound membranes provided in Examples 1-7 and Comparative Examples 1-9:
[0099] (1) Thickness: measured directly by micrometer;
[0100] (2) Young's modulus and loss factor: tested using the material parameter test module (MPM) in KLIPPEL R&D SYSTEM;
[0101] The test data is shown in Table 2:
[0102] Table 2
[0103]
[0104] According to Table 1 and Table 2, the present invention uses chopped carbon fiber as the main substrate, aramid nanofiber as the filling and reinforcing material, obtains a carbon fiber-aramid nanofiber blank through a wet molding process, and then hot presses and shapes it after being impregnated with epoxy glue to obtain a carbon fiber composite sound membrane with high carbon fiber content, ultra-thinness, and excellent mechanical and acoustic properties. As a preferred technical solution of the present invention, the carbon fiber composite sound membrane provided in Examples 1-5 has a thickness of 0.07-0.1mm, a Young's modulus of 22.5-28.4GPa, and a loss factor of 0.015-0.028. The present invention, through the design and mutual combination of specific raw materials and preparation methods, makes the carbon fiber composite sound membrane have a small thickness, high strength and modulus, and a moderate loss factor. When it is applied to a speaker, the speaker has good transient responsiveness, high energy conversion efficiency, and high sensitivity.
[0105] The present invention preferably uses short-cut carbon fibers with an average length of 2-4 mm as the substrate, which has excellent dispersibility and enables the obtained carbon fiber composite sound membrane to have high strength and high modulus. The carbon fiber length of Example 6 is relatively long, resulting in uneven dispersion of the carbon fiber, and a complete and continuous sound membrane wet blank cannot be obtained after filtration. The carbon fiber length of Example 7 is relatively short, and the strength of the obtained carbon fiber composite sound membrane is significantly reduced.
[0106] The present invention uses a specific amount of aramid nanofiber as a filling and reinforcing material, which has a high specific surface area and high surface energy, can be evenly dispersed in a network structure with carbon fiber as the main body, and forms an excellent interweaving and winding effect with carbon fiber, so that the carbon fiber composite sound membrane has high strength, high modulus and suitable damping. When the aramid nanofiber is eliminated in Comparative Examples 1-2, or the weight proportion of the aramid nanofiber is too small, the bonding force between the fibers of the wet blank of the sound membrane becomes significantly weaker, and the fibers shift during hot pressing, resulting in damage to the sound membrane. In Comparative Example 3, the amount of aramid nanofiber used is too much and the carbon fiber is too little, resulting in an increase in the thickness of the sound membrane and a decrease in Young's modulus. Comparative Example 6 uses para-aramid fiber. Due to its smooth surface and no filament separation effect, it cannot produce a wrapping and winding effect with the carbon fiber. The bonding force between the fibers of the wet blank of the sound membrane obtained after filtration is very weak, and the fibers shift during the hot pressing stage, resulting in damage to the sound membrane. Comparative Example 7 uses aramid powder. Although it can fill the pores of carbon fiber, its aspect ratio is small and the fiber shape is not retained. In addition, a large amount of aramid powder will be lost with the water during filtration. Therefore, the fiber bonding force of the wet sound membrane obtained after filtration is very weak, and the fibers shift during the hot pressing stage, causing damage to the sound membrane.
[0107] The present invention adopts a wet molding process to obtain a carbon fiber-aramid nanofiber sound film blank, and then impregnates the epoxy glue, so that the carbon fiber, aramid nanofiber, and epoxy glue are combined in a specific dosage ratio and then hot-pressed. The epoxy resin undergoes a curing reaction, plays a bonding role between the carbon fiber and the aramid nanofiber, makes the carbon fiber composite sound film structure complete and dense, and further improves the strength and modulus of the carbon fiber composite sound film. In comparative example 4, the dosage ratio of epoxy resin to curing agent is too much, the thickness of the obtained carbon fiber composite sound film increases, and the Young's modulus decreases; in comparative example 5, the amount of epoxy resin and curing agent added is too little, resulting in the epoxy glue unable to completely penetrate into the pores of the sound film blank, and the sound film cannot be formed. In comparative example 8, phenolic resin is used to replace the epoxy resin of the present invention. Although the obtained carbon fiber composite sound film has a higher strength, the loss factor is significantly reduced, and the damping performance is reduced. In comparative example 9, water-based polyurethane is used to replace the epoxy resin defined in the present invention, and the Young's modulus of the obtained carbon fiber composite sound film is reduced, and the mechanical properties are deteriorated.
[0108] The applicant declares that the present invention illustrates the carbon fiber composite sound membrane and its preparation method and application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A carbon fiber composite sound membrane, characterized in that: The raw materials for preparing the carbon fiber composite sound membrane include the following components in parts by mass:
2. The carbon fiber composite sound membrane according to claim 1, characterized in that: The average length of the carbon fiber is 2-4 mm; Preferably, based on the total mass of the carbon fiber and the aramid nanofiber being 100%, the mass of the carbon fiber is 85-95%.
3. The carbon fiber composite sound membrane according to claim 1 or 2, characterized in that: The diameter of the aramid nanofiber is 500-990nm; Preferably, the aspect ratio of the aramid nanofiber is 2200-3000.
4. The carbon fiber composite sound membrane according to any one of claims 1 to 3, characterized in that: The curing agent includes an amine curing agent and / or a phenolic curing agent; Preferably, the mass ratio of the epoxy resin to the curing agent is 1:(0.2-0.4).
5. The carbon fiber composite sound membrane according to any one of claims 1 to 4, characterized in that: The thickness of the carbon fiber composite sound membrane is ≤0.12 mm, preferably 0.06-0.1 mm; Preferably, the Young's modulus of the carbon fiber composite sound membrane is ≥21 GPa, and more preferably 22-29 GPa; Preferably, the loss factor of the carbon fiber composite sound membrane is 0.01-0.03, and more preferably 0.015-0.
028.
6. A method for preparing a carbon fiber composite sound membrane according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Dispersing aramid fibers in water for pulping to obtain aramid nanofiber slurry; Evenly mixing the aramid nanofiber slurry and the carbon fiber to obtain a mixed solution; The mixed solution is filtered and dried to obtain a sound membrane blank; The sound membrane blank is immersed in epoxy glue and then hot-pressed to obtain the carbon fiber composite sound membrane; the epoxy glue includes a combination of epoxy resin and curing agent.
7. The preparation method according to claim 6, characterized in that: The beating time is 5-16h; Preferably, during the beating process, the gap between the flying knife and the bottom knife is 0.1-0.2 mm.
8. The preparation method according to claim 6 or 7, characterized in that: Dispersing the aramid nanofiber slurry and carbon fiber in water, and mixing them evenly to obtain a mixed solution; Preferably, the stirring speed of the mixing is 1000-5000 rpm; Preferably, the filtration pressure is 0.1-0.3 MPa; Preferably, the drying temperature is 80-120°C.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The temperature of the hot pressing setting is 150-200°C; Preferably, the heat pressing time is 20-60 min, more preferably 30-45 min.
10. A loudspeaker, characterized in that: The speaker comprises the carbon fiber composite sound membrane as described in any one of claims 1-5.
Citation Information
Patent Citations
Ultrathin carbon fiber sound cone and preparation method and application thereof
CN115895191A
Cited By
High-pitch dome voice diaphragm and preparation method and application thereof
CN121151725A